Geographic pattern of antibiotic resistance genes in the metagenomes of the giant panda. Issue 1 (18th August 2020) - Hu, Ting; Dai, Qinlong; Chen, Hua; Zhang, Zheng; Dai, Qiang; Gu, Xiaodong; Yang, Xuyu; Yang, Zhisong; Zhu, Lifeng
Summary: The rise in infections by antibiotic‐resistant bacteria poses a serious public health problem worldwide. The gut microbiome of animals is a reservoir for antibiotic resistance genes (ARGs). However, the correlation between the gut microbiome of wild animals and ARGs remains controversial. Here, based on the metagenomes of giant pandas (including three wild populations from the Qinling, Qionglai and Xiaoxiangling Mountains, and two major captive populations from Yaan and Chengdu), we investigated the potential correlation between the constitution of the gut microbiome and the composition of ARGs across the different geographic locations and living environments. We found that the types of ARGs were correlated with gut microbiome composition. The NMDS cluster analysis using Jaccard distance of the ARGs composition of the gut microbiome of wild giant pandas displayed a difference based on geographic location. Captivity also had an effect on the differences in ARGs composition. Furthermore, we found that the Qinling population exhibited profound dissimilarities of both gut microbiome composition and ARGs (the highest proportion of Clostridium and vancomycin resistance genes) when compared to the other wild and captive populations studies, which was supported by previous giant panda whole‐genome sequencing analysis. In this study, we provide an example of a potential consensus pattern regarding host population genetics, symbiotic gut microbiome and ARGs. We revealed that habitat isolation impacts the ARG structure in the gut microbiome of mammals. Therefore, the difference in ARG composition between giant panda populations will provide some basic information for their conservation and management, especially for captive populations. Abstract : The wild giant panda in their habitat in Liziping National Nature Reserve, Shimian. The copywight belongs to Liziping National Nature Reserve, Shimian.